Single versus multiple drug focus in substance abuse clinical trials research - Rounsaville, Bruce J. (2003)
Complex patterns of multiple substance use pose clinical and methodological challenges for substance abuse clinical trials research. To increase measurement precision and internal validity, the modal approach has been to target both treatment interventions and outcome assessment to a single class of abused substance. This strategy warrants reconsideration because it entails limitations in recruitment feasibility and generalization of study findings. This report reviews pros and cons of single versus multiple targeted drugs, suggests guidelines for choosing between these strategies and outlines methods for broadening the scope of substance abuse clinical trails to take abuse of multiple substances into account. We recommend that investigators consider moving away from a single drug focus in three ways. First, include systematic assessment of a wide range of psychoactive substance use throughout the trial and evaluate the impact of study treatments on use of all classes of drugs. Second, except where contraindicated, include patients who use and abuse multiple classes of substances even in trials evaluating treatment of a single targeted drug. Third, consider inclusion of polysubstance abusers or those who primarily abuse multiple classes of substances in the same clinical trial. Although many treatment efficacy questions can best be answered by single focus studies, we recommend that such designs be adopted only after less restrictive designs are first considered.